Optimization of the differentiation process of umbilical cord matrix mesenchymal stem cells into hepatocyte-like cells - Silva, Alexandra Martins de Medeiros Vieira da (2013)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2013